The role of contractors in the uptake of precision farming—A spatial economic analysis. Issue 1 (16th February 2022) - Wang, Yanbing; Huber, Robert; Finger, Robert
Abstract: Contractors will play a vital role in providing farms with access to new precision farming technologies, especially in small-scale farming systems. We investigate the impact of spatial competition among contractors on the uptake of precision farming and the effectiveness of policy interventions, considering alternative spatial price schedules. Conceptual analyses show that a lack of spatial competition among contractors hinders uptake of precision farming technology. The effectiveness of policy interventions to support precision farming also depends on the market structure and contractors' price schedules. In addition, we illustrate the results in a Swiss case study based on a specific contractors' service market of plant protection technologies.